2011
DOI: 10.1021/es201548c
|View full text |Cite
|
Sign up to set email alerts
|

Hexabromocyclododecane: Current Understanding of Chemistry, Environmental Fate and Toxicology and Implications for Global Management

Abstract: Hexabromocyclododecane (HBCD) is a globally produced brominated flame retardant (BFR) used primarily as an additive FR in polystyrene and textile products and has been the subject of intensified research, monitoring and regulatory interest over the past decade. HBCD is currently being evaluated under the Stockholm Convention on Persistent Organic Pollutants. HBCD is hydrophobic (i.e., has low water solubility) and thus partitions to organic phases in the aquatic environment (e.g., lipids, suspended solids). It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
156
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(164 citation statements)
references
References 100 publications
5
156
2
1
Order By: Relevance
“…The reported water solubility of TBBPA, varying from 0.17 to 4.2 mg/L at 25°C (due to transformation from nonionic to ionic forms) (Kuramochi et al, 2008), is much higher than those of the three HBCD diastereoisomers (0.002-0.05 mg/L) (Marvin et al, 2011), suggesting a preferred transport via aqueous phase for TBBPA. Whereas HBCD has vapor pressure 6.3 Â 10 À5 Pa at 21°C (Marvin et al, 2011), which is several order of magnitude higher than that of TBBPA (4.72 Â 10 À9 Pa at 25°C) (Kuramochi et al, 2008). Atmospheric transport and deposition may play a more important role in moving HBCD from sources to remote regions.…”
Section: Concentrations and Spatial Distributionsmentioning
confidence: 96%
“…The reported water solubility of TBBPA, varying from 0.17 to 4.2 mg/L at 25°C (due to transformation from nonionic to ionic forms) (Kuramochi et al, 2008), is much higher than those of the three HBCD diastereoisomers (0.002-0.05 mg/L) (Marvin et al, 2011), suggesting a preferred transport via aqueous phase for TBBPA. Whereas HBCD has vapor pressure 6.3 Â 10 À5 Pa at 21°C (Marvin et al, 2011), which is several order of magnitude higher than that of TBBPA (4.72 Â 10 À9 Pa at 25°C) (Kuramochi et al, 2008). Atmospheric transport and deposition may play a more important role in moving HBCD from sources to remote regions.…”
Section: Concentrations and Spatial Distributionsmentioning
confidence: 96%
“…On the basis of empirical data primarily, the half-life of HBCD in soil is ≥182 days (Environment Canada, 2011). Half-life in air >2 days 3.7 to 6.33 (Chen et al, 1984) 0.4 to 5.2 (Marvin et al, 2011) Half-life in water >60 days 3 to 300 days (Mackay et al, 1997) 60 to 130 days (Marvin et al, 2011) Half-life in aquatic sediments >180 days 90 days (WWFC, 1999) 0.9 to 12.6 years (Helm et al, 2002) 125-191 days (EC, 2008) Half-life in soil >180 days <180-1146<180- (IPCS, 1991 6.9 to 63 days (Davis et al, 2005) ≥182 days (Environment Canada, 2011) Half-life in biota (days/years) none 7 to 10 years (humans) (Zou and Matsumura, 2003) 23 to 219 days (humans) (Schecter et al, 2012) 1 to 17 days (mice) (Schecter et al, 2012) 53 to 136 days (fish) When released to the environment, HBCD isomers will adsorb onto solid particles of sediments and soil . Though there is a predominance (>90%) of γ-HCBD in the environment compared to α-and β-HBCD, α-HBCD often has the highest prevalence in biota, followed by β-HBCD (Birnbaum and Staskal, 2004).…”
Section: Persistencementioning
confidence: 99%
“…1 Commercial HBCD mixtures mainly consist of three racemic isomers (±) α-(6%), β-(10%), and γ-HBCDs (70%). 1,2 In the last few decades, HBCDs have been frequently detected in environmental matrices and biota samples. 1−3 HBCDs have been shown to be bioaccumulative in aquatic and terrestrial food webs 4,5 and were reported to exert toxic effects on the reproductive success and embryonic development of avian species, 6−8 which raise more environmental concern about HBCDs.…”
Section: ■ Introductionmentioning
confidence: 99%